Teachers Teaching Management During Belajar dari Rumah (BDR) Policy In Higher Education: A Piece of Teacher Sharing Ways - Suryawahyuni Latief; Santi Hendrayani; Samsuddin Samsuddin (International Journal on Advanced Science, Education, and Religion, 2021)
Teaching is an educator activity in the learning process, which aims to develop the potential that students have in the form of knowledge, skills, and attitudes. Since the Covid 19 pandemic, the government has issued a policy of "Belajar Dari Rumah" (BDR) as an effort to overcome the spread of the virus. Teaching in accordance with BDR policy makes educators at private universities in Jambi city who do not have a Learning Management System (LMS) conduct teaching management in accordance with their expertise and knowledge. This study aims to describe the experience of educators in universities who do not have LMS in managing teaching during the Covid 19 pandemic so that learning can run according to learning objectives using a qualitative descriptive approach, involving ten educators with different scientific fields and courses. This research uses a qualitative research method involving ten educators from private universities in Jambi who do not have LMS. Data have collected through observations, interviews, and documents. The data collected have analyzed through the stages of reducing data, displaying data, and drawing conclusions in accordance with research objectives. The data analyzed is using the technique validity of data through data triangulation. The study found that the management of educator teaching in private universities in Jambi city who do not have LMS is implemented BDR policies during the pandemic period following the established implementation rules without leaving the meaning of learning and learning process standards that have set out in government regulations through the stage of teaching management. Keywords: Work from Home, Learning, Belajar dar Rumah, Teaching Management